2022
DOI: 10.1037/pas0001113
|View full text |Cite
|
Sign up to set email alerts
|

MMPI-3 scale predictors of reactions to ostracism in a sample of racially diverse college students.

Abstract: We examined the ability of the Minnesota Multiphasic Personality Inventory-3 (MMPI-3) scales to predict reflexive reactions to rejection elicited via a Cyberball task. In an effort to expand the criterion-related and incremental validity knowledge of the MMPI-3, we specifically focused on scale associations with the following adverse reflexive reactions: feelings of rejection, low positive and high negative affect, and high perceived threats to social needs. We hypothesized 10 substantive scales that assess ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
1
0
0
Order By: Relevance
“…First, a relatively small percentage of participants produced invalid MMPI-3 protocols in the In-Person Pre-COVID-19 Onset, In-Person Post-COVID-19 Onset, and Remote groups (8.8%, 11.7%, and 6.2%, respectively). These rates are comparable or even favorable in comparison with those of recently published studies on the MMPI-3 using undergraduate student samples (e.g., Anestis et al, 2022 [20.1%]; Brown & Sellbom, 2021 [7.6%]; Marek & Anderson, 2022 [12.2%]). However, chi-square analyses indicated that the Remote group produced a significantly smaller proportion of invalid protocols than the In-Person Post-COVID-19 Onset group.…”
Section: Discussionsupporting
confidence: 81%
“…First, a relatively small percentage of participants produced invalid MMPI-3 protocols in the In-Person Pre-COVID-19 Onset, In-Person Post-COVID-19 Onset, and Remote groups (8.8%, 11.7%, and 6.2%, respectively). These rates are comparable or even favorable in comparison with those of recently published studies on the MMPI-3 using undergraduate student samples (e.g., Anestis et al, 2022 [20.1%]; Brown & Sellbom, 2021 [7.6%]; Marek & Anderson, 2022 [12.2%]). However, chi-square analyses indicated that the Remote group produced a significantly smaller proportion of invalid protocols than the In-Person Post-COVID-19 Onset group.…”
Section: Discussionsupporting
confidence: 81%